2013
DOI: 10.1007/s40489-013-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Video Modelling and Scripts in Teaching Conversational Skills to Individuals with Autism Spectrum Disorders

Abstract: Individuals with autism spectrum disorders (ASD) have difficulties acquiring social skills without direct intervention. This article provides a review of research on the use of video modelling and scripts to improve the verbal conversational skills of individuals with ASD. The studies reviewed included participants with a diagnosis of ASD and reported empirical data on some aspect of verbal conversation. Percentage of nonoverlapping data and percentage exceeding the mean metrics were calculated for each study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
(110 reference statements)
2
3
0
1
Order By: Relevance
“…One explanation for the slight difference in the PND values between our review and Bellini and Akulian’s might be the different inclusion and exclusion criteria and decision rules. Furthermore, the overall PEM mean score of 0.82 from our review was consistent with the PEM mean score of 0.82 as reported by Sng and colleagues (2014). Overall, our summative evaluation supports previous research in concluding that VM is an EBP for improving social communication skills of individuals with ASD using the WWC criteria.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…One explanation for the slight difference in the PND values between our review and Bellini and Akulian’s might be the different inclusion and exclusion criteria and decision rules. Furthermore, the overall PEM mean score of 0.82 from our review was consistent with the PEM mean score of 0.82 as reported by Sng and colleagues (2014). Overall, our summative evaluation supports previous research in concluding that VM is an EBP for improving social communication skills of individuals with ASD using the WWC criteria.…”
Section: Discussionsupporting
confidence: 87%
“…These findings are consistent with those of studies that employed nonoverlapping metrics and concluded that VM interventions were effective in increasing social communication skills of individuals with ASD. The overall mean PND value of 0.74 from our review was similar to the mean PND value of 0.77 as reported by Bellini and Akullian (2007) and the mean PND value of 0.72 as reported by Sng and colleagues (2014) for using VM interventions to increase social communication. One explanation for the slight difference in the PND values between our review and Bellini and Akulian’s might be the different inclusion and exclusion criteria and decision rules.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A range of outcomes have been targeted, such as turn taking, initiating interaction, recognising emotions and understanding theory of mind (Begeer et al, 2011;Matson et al, 2007;Rieth et al, 2014). Well-established interventions include Social Stories™ (Karkhaneh et al, 2010), video modelling (Sng et al, 2014), pivotal response training (Koegel et al, 2016), social skills groups (Reichow et al, 2012) and peer-mediated behavioural interventions (Laushey & Heflin, 2000). There is increasing evidence that, at least in some contexts, these interventions can help autistic children to utilise neurotypical social skills but the duration, generalisability and precise mechanism of change remains unclear (McConnell, 2002).…”
Section: Social Skills Interventionsmentioning
confidence: 99%
“…Alanyazında OSB'li bireylere yönelik yalnızca video model uygulaması kullanılarak yürütülen araştırmalar incelendiğinde, video model uygulamasının OSB'li bireylere matematik becerileri (Burton, Anderson, Prater ve Dyches, 2013;Jowett vd., 2012), tuvalet becerileri (Keen, Brannigan ve Cuskelly 2007), ev kazalarına karşı ilk yardım becerileri, soğuk içecek hazırlama ve sunma gibi günlük yaşam becerileri (Ergenekon, 2012;Gülsöz, 2014;Shipley-Benamou vd., 2002), iş görüşmesi yapma gibi iş ve meslek becerileri (Bahçalı, 2016;Rausa, Moore ve Anderson, 2016), oyun oynama becerilerinin öğretiminde (Besler ve Kurt, 2016;Lydon, Healy ve Leader, 2011;Reagon vd., 2006;Sancho vd., 2010), karşılıklı konuşma becerilerinin kazandırılmasında (Sherer vd., 2001;Sng, Carter ve Stephenson, 2014), sosyal etkileşim başlatma ve sürdürme becerileri (Alzyoudi, Sartawi ve Almuhiri, 2015;Nikopoulos ve Keenan, 2003Pektaş Karabekir, 2016;Wilson, 2013), taklit becerileri (Kleeber ve Mirenda, 2010;Rayner, 2011), üst geçit kullanarak karşıdan karşıya geçme becerisinde (Yavuz, 2017) ve yüz ifadelerini adlandırma becerilerinin (Akmanoglu, 2015) öğretiminde etkili olduğunu gösteren çalışmalar mevcuttur.…”
Section: Introductionunclassified